Catalysing actionable knowledge to enhance next-generation ACP agribusiness through digitalisation - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2018)
Drones, satellite images, advisory services, market access platforms, financial services….over the past few years, digitalisation has been applied to agribusiness through many initiatives, projects, activities being developed, piloted, tested and tried in ACP countries.